KOLERASI ANTARA TINGKAT KEBUGARAN JASMANI TERHADAP KEMAMPUAN AKADEMIK SISWA KELAS X MAN 2 KOTA JAMBI - M. Farhan Wahbi; Atri Widowati; Bangkit Yudho Prabowo (Jurnal Riset Multidisiplin Edukasi, 2025)
This study examines the correlation between physical fitness levels and academic performance of grade X students at MAN 2 Kota Jambi. The aim is to understand how variations in physical fitness affect students' academic ability. Involving 36 students from 12 different classes, this study uses statistical methods, including normality and homogeneity tests, to ensure data validity. The results will reveal the relationship between physical fitness and academic performance and offer insights into the importance of physical health in education. This research emphasizes that a healthy lifestyle and physical fitness can enhance students' academic achievement, encouraging schools to incorporate physical fitness into their academic programs. Overall, this study contributes to understanding how physical well-being can influence educational outcomes.